POTENSI DAN PRODUKSI PAKAN RUSA TIMOR (Cervus timorensis) DI KAMPUS UNIVERSITAS RIAU - Ano Riyadi; Defri Yoza; Sonia Somadona (Fakultas Pertanian, Universitas Riau, 2021)
Timor deer (Cervus timorensis) is the second largest tropical deer after sambar. Compared to other Indonesian tropical deer, the timor deer (Cervus timorensis) is unique in that it is a deer that has many sub species, with a wide spread area. Timor deer (Cervus timorensis) are widely bred in various locations because they have high economic value, in which all parts can be utilized. The potential of timor deer can be developed as part of environmental services that have high value as recreational objects. The purpose of this study was to determine the potential of timor deer feed (Cervus timorensis) at the University of Riau and determine the production of timor deer feed (Cervus timorensis) at the University of Riau. The study was conducted at a prospective location for timor deer breeding (Cervus timorensis), Riau University campus covering an area of approximately 2.07 ha. Sampling was carried out using a plot of 41 plots, with a size of 1 m x 10 m. Riau University has potential as a location for timor deer breeding (Cervus timorensis). Production of all types of deer feed in captive breeding sites amounted to 2,878.67 gr/m.